Pengaruh Kualitas Pelayanan Dan Citra Merek Terhadap Kepuasan Konsumen Pada PT. Permodalan Nasional Madani Cabang Cibadak - Muhamad Abian Nurdiansyah (Journal Economic Excellence Ibnu Sina, 2023)
The aim of the research was to determine cosumer respons and and the effect of service quality and brand image on customer satisfaction at PT Permodalan Nasional Madani Cibadak Branch simultaneously and individually. The method used in this research is the survey method. The type of research is descriptive and verification. The sample size used in this study was 100 consumers. The data analysis method uses multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis and simultaneous and partial hypothesis testing. The results showed that simultaneously and individually service quality and brand image have a positive and significant effect on customer satisfaction at PT. Permodalan Nasional Madani branch Cibadak.